Incarceration for Reformation or Deformation? - Amali, Sadiq Ewaoda (2021)
The reason for imposing incarceration is to punish offenders for violating societal norms and values. As a means of punishment, it is deliberately inflicted on an offender, which serves as a deterrence to would-be offenders. This could help in inculcating good morals on offenders, thereby altering him or her from a nonconforming individual to a conforming one. Despite the good intention of imposing incarceration, it has contradicted its cardinal objective which has resulted in some unintended consequences such as inability to secure employment as a result of stigmatization, aiding the collapse of marriages among others. With the above-stated consequences of incarceration, penal institutions instead of instilling the positive goal of incarceration on inmates, on the contrary, it has served as a punishment ground with degrading treatment imposed on inmates by correctional officials coupled with the dehumanizing state of most penal institutions. This article concludes that incarceration has a long term effect on the positive life of offenders and recommends that concerted efforts should be made in reintegrating ex-offenders, discouraging the idea of tagging, and make ample efforts on how ex-offenders can secure payable jobs upon regaining freedom